Presentation and Sources of Pediatric Odontogenic Infection - Sahar Abdualkader Ismaeel; Saif Saadedeen Abdulrazaq; Reem Fadhil Abbas (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background and Objectives: The causes, clinical presentation and management of the odontogenicinfection in children during the mixed and premixed dentition period should be thoroughly studied as itdiffers from that of adults. The study aimed to identify the common sources and presentation of dentalinfection in those children.Methods: The selected cases were 122 (54 females and 68 males). All cases presented with odontogenicinfection, examined meticulously to diagnose the source of infection.Results: The mean age was 6.5 years old (The age range was 3-10 years). The most common source ofinfection in primary teeth was the second primary molars (38 cases; 31.1%). The most common source ofinfection in permanent teeth was the first permanent lower molars (30 cases; 24.6%). The most commonpresentation was vestibular swelling (56 cases; 45.9%).Conclusion: Dental care should be provided early especially to the permanent first molars in children toavoid losing them. Teamwork between the oral surgeon and the general pediatrician is necessary for bettermanagement.